A preliminary investigation on the biocompatibility studies of cellulose from oil palm residue as surgical biomaterial - Mohd Khairi, Md Daud (Pusat Pengajian Sains Perubatan, 2013)
Cellulose is the world's most abundant natural, renewable, and biodegradable polymer. An in vitro biocompatibility test was carried out to look at cytotoxicity characteristic of our locally produce cellulose phosphate on osteoblast and chondroblast cell lines. Cellulose samples were prepared from the oil palm residues. The cell line used in this study was human osteoblast and Chondroblast obtained from the American Type Culture Collection. An in vitro cytotoxicity test was carried out on the cellulose material using extraction/indirect methods. For human osteoblast, the concentration for IC-50 was determined at 60mg/ml while no IC-50 was observed for human chondroblast cells. The results suggest the biocompatibility of cellulose as biomaterial on human cell lines is good and not cytotoxic. Cellulose is the world's most abundant natural, renewable, and biodegradable polymer. Polysaccharides, like cellulose, are the polymer group with the longest and widest medical applications experience because of their unique properties: nontoxicity, water solubility or high swelling ability by simple chemical modification, stability to temperature and pH variations, and a broad variety of chemical structures 1 . The biocompatibility of some cellulosics is well documented. Oxidized cellulose is used as a wound dressing2 . Regenerated cellulose hydrogels (cellulose regenerated by the viscose process-CRV) have been investigated as implantable materials in orthopaedic surgery. Their good matching with mechanical properties of bone, as well as their biocompatibility has been I demonstrated3 Chemically modification via phosphorylation further stimulates bone induction4. Research innovation on the use of cellulose and its derivatives in medical application was conceived and developed all over the country but thus far not in Malaysia. In vitro cell culture methods are the basic starting point whereby biological responses to materials are determined initially, as required by a number of standardization agencies5. These methods have the advantages of simplicity, good sensitivity and reproducibility and are widely used in the initial evaluation of biocompatibility of materials. In this study, an in vitro biocompatibility test was carried out to look at cytotoxicity characteristic of our locally produce cellulose phosphate on osteoblast and chondroblast cell lines. ific